FINANCIAL RATIO ANALYSIS IN PREDICTING FINANCIAL DISTRESS CONDITIONS BUMN COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE DURING THE COVID-19 PANDEMIC WITH USING THE ALTMAN Z-SCORE METHOD - Aslam Rayuda; Nisrul Irawati; Isfenti Sadalia (PT. Radja Intercontinental Publishing, 2023)
The research is that having sufficient working capital is very important for a company because with sufficient working capital it is possible for the company to operate as economically as possible and the company does not experience difficulties or face dangers that may arise due to a crisis or financial chaos. Companies with negative net working capital have a high probability of facing difficulties in paying off their short-term liabilities, because there are not enough current assets to cover these liabilities. A cumulative profitability measure that reflects a company's age as well as the company's earnings power. Profitable operations and debt reduction are characterized by companies retaining profits or reinvesting operating profits. Low retained earnings can indicate a bad business year or reduced company life. This ratio is an indicator that shows management efficiency in managing production, sales, administration and other activities. The lower the EBITTA ratio value indicates the lower productivity of assets in generating profits. The EBIT to total assets ratio shows the effectiveness of using all assets in generating company sales. The greater the value of this ratio, the more effective the management of all assets owned by the company. Earnings Before Interest and Tax to Total Assets (EBITTA) is one of the profitability ratios. This analysis is used to measure a company's ability to manage its resources effectively which can be seen from the results of its sales and investments. The EBITTA ratio measures whether a company's assets are used rationally to generate profits from its operating activities. If the resulting ratio is high, then the company's assets have been used rationally so that it can reduce the occurrence of Financial Distress. On the other hand, a low EBITTA ratio indicates that the company is likely to experience financial distress. The implication of this research is that this ratio is used to measure management's ability to use assets to generate sales and describe the turnover rate of all company assets. This ratio, which has a positive value, is a sign that the company has a good ability to use assets to generate sales and has a high level of asset turnover.